Charting platform capitalism: Definitions, concepts and ideologies. (23rd February 2022) - Liang, Yin; Aroles, Jeremy; Brandl, Bernd
Abstract: The term 'platform capitalism' captures a dynamic set of new work modalities that are mediated by platforms and have been brought about through advances in Information and Communication Technologies, adjustments in consumption modes and preferences, and changes in how work is conceived. Beyond work‐related changes, the ascent of platform capitalism reflects wider societal and political as well as economic changes. While research on platform capitalism and its manifold manifestations abounds, there is a lack of consensus in the literature regarding its key features and characteristics. Seeking to provide conceptual clarity and to contribute to efforts of theorization, we here analyse four main facets of platform capitalism, namely, crowdsourcing, sharing economy, gig economy and platform economy. We review key definitions of each term and provide an overview of their distinctive features. This allows us to identify both similarities and differences in the framing of these four terms. We also delve into the ideologies underlying these four terms, thus providing a critique of the neophilia characterizing the discourse framing platform capitalism.